Treatment Outcome of Ponseti Method in the Management of Club Foot at Komfo Anokye Teaching Hospital, Ghana: A Retrospective Study - , Hosea Boakye; , Afiriyie Nsiah; , Abebrese Thomas; , Ajediran Idowu Bello (Archives of Current Research International, 2016)
Background: Ponseti method is an established conservative treatment for idiopathic clubfoot in children world-wide. Yet, no data are available to quantify its effectiveness for reference in Ghana. Aim: To explore the effectiveness of Ponseti method in the management of clubfoot at a Tertiary Health Facility in Ghana. Materials and Methods: The 6-year single arm retrospective cohort study involved a review of clinical folders of babies with club feet. The age range of the children was between 0 and 6 months. They were managed using Ponseti method from 2008 to 2013 at Komfo Anokye Teaching Hospital Clubfoot Clinic. Demographic data and Pirani scores were retrieved from their folders. Pirani scores served as evaluation index through which the treatment outcome of the Ponseti method was evaluated. Data were gleaned to descriptive and interferential statistics. Results: A total of 271 folders of children with club foot were retrieved and reviewed. An average of 5 casts was applied to correct a child’s club foot deformity prior to the prescription of Foot Abduction Brace. Pirani score for mid-foot was significantly lower than that of the hind-foot whilst males had significantly higher number of casts than the female. The number of casts required for correction was positively correlated with the age of the children (r=0.346) and their Pirani scores (r= 0.514, right foot; r= 0.415, left foot). Conclusion: Ponseti method is effective in the management of clubfoot whilst age and initial Pirani scores were the determinants of the number of casts required and indication for tenotomy respectively.